Recto-Anal Junction (RAJ) and Fecal Microbiomes of Cattle Experimentally Challenged With Escherichia coli O157:H7 - Mir, Raies A.; Schaut, Robert G.; Looft, Torey; Allen, Heather K.; Sharma, Vijay K.; Kudva, Indira T. (Frontiers in Microbiology, 2020)
Cattle are the asymptomatic reservoirs of Escherichia coli O157:H7 (O157) that preferentially colonizes the bovine recto-anal junction (RAJ). Understanding the influence of O157 on the diversity of the RAJ microbiota could give insights into its persistence at the RAJ in cattle. Hence, we compared changes in bovine RAJ and fecal microbiota following O157 challenge under experimental conditions. Cattle were either orally challenged (n=4) with1010 CFU of a streptomycin-resistant O157 strain 86-24, or mock-challenged (n=4) with phosphate buffered saline. Rectoanal mucosal swab (RAMS) and fecal samples were collected at different time points for analysis. Alpha diversity measures (Chao1 species richness and Shannon diversity index) were found to be significantly different between RAMS and fecal samples but not influenced by O157 challenge. The Firmicutes to Bacteroidetes (F: B) ratio was higher in RAMS samples from O157 colonized animals and this may have influenced the consistent yet decreased O157 colonization at the RAJ. Specific bacterial genera that were present in relative low abundance in fecal and RAMS microbiota did not affect overall microbial diversity but were associated with O157 colonization. Differential abundance analysis of genera in samples from O157 shedding cattle indicated significantly higher relative abundance of Paenibacillus and Fusobacterium in RAMS, and Tyzzerella in fecal samples. Mock-challenged cattle showed higher relative abundance of Intestinimonas and Citrobacter in RAMS samples, and Succinivibriio, and Prevotella 1 in fecal samples. These results suggest that O157 challenge exerts transient influence on the intestinal microbial community which in turn might promote O157 colonization in a site-specific manner.